First-In-Class Small Molecule ONC201 Induces DR5 and Cell Death in Tumor but Not Normal Cells to Provide a Wide Therapeutic Index as an Anti-Cancer Agent - Allen, Joshua E. (PLoS One, 2015)
We previously identified ONC201 (TIC10) as a first-in-class orally active small molecule with robust antitumor activity that is currently in clinical trials in advanced cancers. Here, we further investigate the safety characteristics of ONC201 in preclinical models that reveal an excellent safety profile at doses that exceed efficacious doses by 10-fold. In vitro studies indicated a strikingly different dose-response relationship when comparing tumor and normal cells where maximal effects are much stronger in tumor cells than in normal cells. In further support of a wide therapeutic index, investigation of tumor and normal cell responses under identical conditions demonstrated large apoptotic effects in tumor cells and modest anti-proliferative effects in normal cells that were non-apoptotic and reversible. Probing the underlying mechanism of apoptosis indicated that ONC201 does not induce DR5 in normal cells under conditions that induce DR5 in tumor cells; DR5 is a pro-apoptotic TRAIL receptor previously linked to the anti-tumor mechanism of ONC201. GLP toxicology studies in Sprague-Dawley rats and beagle dogs at therapeutic and exaggerated doses revealed no dose-limiting toxicities. Observations in both species at the highest doses were mild and reversible at doses above 10-fold the expected therapeutic dose. The no observed adverse event level (NOAEL) was ≥42 mg/kg in dogs and ≥125 mg/kg in rats, which both correspond to a human dose of approximately 1.25 g assuming standard allometric scaling. These results provided the rationale for the 125 mg starting dose in dose escalation clinical trials that began in 2015 in patients with advanced cancer.